Agriculture in an urbanizing society. proceedings of the sixth AESOP Conference on Sustainable Food Planning : "Finding spaces for productive cities" November 5-7, 2014, Leeuwarden, The Netherlands /: proceedings of the sixth AESOP Conference on Sustainable Food Planning : "Finding spaces for productive cities" November 5-7, 2014, Leeuwarden, The Netherlands. Volume one : (2016) - Unknown
No abstract available